PENGEMBANGAN BAHAN AJAR TRIGONOMETRI BERBASIS ANIMASI PADA MASA PANDEMI COVID-19 - Wahyu Setiawan; Luthfiyani Fauziyyah Noor Hakim; Gerry Filiestianto (IKIP Siliwangi, 2021)
In order to reduce and break the chain of spread of the covid-19 virus, the government through the minister of education and culture makes a policy if the teaching and learning activity process is carried out daring. In the daring teaching and learning process, a teacher is required to be able to make interesting and interactive teaching materials that can be presented daring. A lot of research has proven the advantages of animation-based teaching materials, but currently there are still few trigonometry-based teaching materials. The purpose of this research is to develop animation-based trigonometric teaching materials during the Covid-19 epidemic. This research consists of sessions on define, design, and develop. The data processing technique is in the form of qualitative data including the results of filling out the validation form, the teacher practicality evaluation form, the student practicality evaluation form and the learning application observation form. The observation form is divided into 5 options, each evaluation score 1, score 2, score 3, score 4 score . 5. The results of this research are that this teaching material is suitable for use with very feasible criteria with an evaluation score of 85%, and media experts give a score of 78% which is categorized as feasible. In the small group trial, an average of 80 was obtained with the very feasible category. As well as large group trials obtained an average of 72 with the feasible category. Thus this animation-based trigonometric teaching material can be used as an alternative to teaching materials that attract students' interest.